Trust Differences Across National-Societal Cultures: Much to Do, or Much Ado about Nothing? - FERRIN, Don (Institutional Knowledge at Singapore Management University, 2010)
Does trust and its development, functions and meaning, differ between people from different national–societal cultures? There is considerable anecdotal evidence and some theoretical argumentation to suggest it does, but are these supported by empirical research? This chapter reviews the available empirical evidence on the effects of national–societal culture on interpersonal trust. It focuses largely on quantitative empirical evidence to consider the extent to which, and the ways in which, interpersonal trust differs across national–societal cultures. In every category of our review we found evidence of cross-cultural differences, particularly on generalized trust, and also evidence of trust universals across cultures. In evaluating these findings, we conclude that trust may operate as a variform universal and variform functional universal. We conclude with two proposed routes for future research, and implications for practice.